Strategies of teaching literature by a novice and an experienced lecturer: two case studies / Jasmin Hassan - Hassan, Jasmin (2011)
The study investigates the teaching strategies utilized by novice and senior lecturers in teaching literature in the ESL context. Two lecturers; one senior and one novice lecturer from the Faculty of Education, Universiti Teknologi MARA (UiTM) Shah Alam took part in the study. The lecturers were observed three times respectively to investigate the strategies they use for three parts of the lesson: introduction, while-reading and conclusion. Interviews via e-mail were also earned out to investigate factors that influence the lecturers* decision in choosing activities and to what extent the lecturers are satisfied with their teaching. The study found that the senior lecturer had more structured lessons and was more consistent with strategies used in class for teaching literature as compared to the novice lecturer. It was also found that lessons conducted by the senior lecturer tend to be teacher-centered while those conducted by the novice lecturer tends to be learner-centered. The senior lecturer believed in the strategies he has been using all these years to be the best ones to achieve his teaching objectives and therefore sees no need for change. The novice lecturer however stated that he changes his strategies according to his students" interests and ability. He also feels that his strategies has room for improvement and is open to go for further training courses in teaching literature. The senior lecturer on the other hand feels the opposite. Therefore the findings of this study indicates that there are differences in teaching activities and strategies applied by senior and novice lecturers as well as differences in their beliefs about these strategies. To conclude, these findings offer insights into how senior and novice lecturers teach literature and is hoped to be beneficial for teachers, teacher-trainees as well as administrative staffs of institutions of higher learning.